Emotional Intelligence and Employee Outcomes among Special School Teachers in Kerala: An Integrated CFA and Structural Equation Modelling Approach (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Emotional intelligence has become an essential psychological asset impacting job results in emotionally taxing fields, including special education. This study investigates the structural links between emotional intelligence and employee outcomes among special school teachers in Kerala, employing a CFA–SEM integrated analytical approach. Data were gathered from 606 special school teachers using a structured questionnaire and evaluated using confirmatory factor analysis to validate the measurement model, subsequently employing covariance-based structural equation modeling to assess the proposed correlations. The findings demonstrate that emotional intelligence exerts a substantial and favorable influence on job satisfaction, job commitment, job performance, and organizational citizenship behavior. Mediation research indicates that emotional intelligence has a substantial direct impact on job commitment, although job satisfaction does not significantly mediate this link. These results indicate that emotional intelligence serves as an inherent attribute that directly improves professional efficacy, rather than functioning through intermediary processes. The study emphasizes the significance of enhancing emotional intelligence to elevate employee outcomes and maintain efficacy in special education settings.